Integral-Sliding-Mode-Observer-Based Structure and Motion Estimation of a Single Object in General Motion Using a Monocular Dynamic Camera - Chwa, Dongkyoung (IEEE Access, 2020)
An integral sliding mode observer (ISMO)-based method for estimating the structure and motion (SaM) of an object in general motion is proposed using a monocular dynamic (moving) camera. As the unknown range and object velocity can be considered as disturbances and should be quickly estimated, it is necessary to maintain the robustness against these disturbances from the start by eliminating the reaching mode. Therefore, the ISMO-based method is proposed on the basis of a relative camera-object motion model. By formulating the relative motion model with three-dimensional measurable state variables, three unknown components among the range, unknown object velocity components, and unknown camera velocity components can be estimated by the proposed method in the following cases: i) the camera is in dynamic motion and the object is in semigeneral motion [i.e., initially static (stationary) and then in general (static or dynamic) motion], ii) the camera is in dynamic motion and the object is in general motion within a constrained space, and iii) both the object and camera are in general motion within a less constrained space when the range information is available. Simulation and experimental results demonstrate that the range and object velocity can be estimated with a satisfactory transient response using a monocular dynamic camera.
Keywords: Dynamic camera; Integral sliding mode; object in general motion; Relative motion dynamics; Structure and motions; Camera-object relative motion dynamics; integral sliding mode observer; monocular dynamic camera; object in general motion; structure and motion estimation